The specific DNA barcodes based on chloroplast genes for species identification of Orchidaceae plants - Huili Li (Nature Portfolio, 2021)
Abstract DNA barcoding is currently an effective and widely used tool that enables rapid and accurate identification of plant species. The Orchidaceae is the second largest family of flowering plants, with more than 700 genera and 20,000 species distributed nearly worldwide. The accurate identification of Orchids not only contributes to the safe utilization of these plants, but also it is essential to the protection and utilization of germplasm resources. In this study, the DNA barcoding of 4 chloroplast genes (matK, rbcL, ndhF and ycf1) were used to provide theoretical basis for species identification, germplasm conservation and innovative utilization of orchids. By comparing the nucleotide replacement saturation of the single or combined sequences among the 4 genes, we found that these sequences reached a saturation state and were suitable for phylogenetic relationship analysis. The phylogenetic analyses based on genetic distance indicated that ndhF and ycf1 sequences were competent to identification at genus and species level of orchids in a single gene. In the combined sequences, matK + ycf1 and ndhF + ycf1 were qualified for identification at the genera and species levels, suggesting the potential roles of ndhF, ycf1, matK + ycf1 and ndhF + ycf1 as candidate barcodes for orchids. Based on the SNP sites, candidate genes were used to obtain the specific barcode of orchid plant species and generated the corresponding DNA QR code ID card that could be immediately recognized by electronic devices. This study provides innovative research methods for efficient species identification of orchids. The standardized and accurate barcode information of Orchids is provided for researchers. It lays the foundation for the conservation, evaluation, innovative utilization and protection of Orchidaceae germplasm resources.